Insertion sequences and DNA transposition - Reznikoff, William (Henry Stewart Talks, 2008)
Insertions sequences, A major form of mobile genetic elements in eubacteria and archaebacteria, Insertion sequences move via DNA transposition, Insertion sequences cause genome changes (insertions, deletions, inversions and chromosome fusions) and facilitate the horizontal transfer of genes, Related processes include integration of HIV-1 DNA